Magical beasts and unbelievable monsters illustrated by Victoria de Larrea. - Woods, Geraldine (EMC Pub., 1980)
Discusses the dragon, unicorn, phoenix, kraken, roc, griffon, Sasquatch, Yeti, Loch Ness monster, and other mysterious beasts.